The Association of Pre-stroke Psychosis and Post-stroke Levels of Health, Resource Utilization, and Care Process: A Register-Based Study - Willers, Carl; Sunnerhagen, Katharina S.; Lekander, Ingrid; von Euler, Mia (Frontiers in Neurology, 2018)
Background While approximately one percent of the global population is formally diagnosed with psychosis or schizophrenia, the actual number is expected to be significantly higher. These patients often consume more healthcare resources and have poorer somatic health. In this study, we analyze potential differences in health, resources, and care process between stroke patients with and without a previous diagnosis of psychosis or schizophrenia. Methods Ischemic stroke patients from seven regions in Sweden were identified via ICD-10 codes (I63.0-9) in regional administrative systems and the Swedish Stroke Register, and approximately 70% of all ischemic stroke cases in Sweden during 2008-2011 were included (n=46,350). Relevant patient-level data from national registries were linked to enable multivariate regression analysis, including data on socioeconomics, mortality, municipality services, and filled prescriptions. History of psychosis or schizophrenia was defined via ICD-10 codes F20-29 (n=389). Results Patient-reported functional outcomes at three months and one year were significantly lower in the psychosis subgroup, and stroke recurrence was higher. Patients with pre-stroke psychosis did not receive of the same levels of reperfusion treatment as the non-psychosis group. Time at the stroke unit was the same, as were first-year levels of somatic care, but dispensation of antihypertensives was less common. Conclusion Our findings emphasize the importance of taking mental comorbidity into account during stroke treatment as well as when evaluating indicators for health, resources, and the care process, since mental comorbidity such as psychosis may have a significant impact the year preceding and the year succeeding the stroke event.